Magnitude of sugar-sweetened beverage consumption and associated factors among women aged 15-49 years old in two Sub-Saharan African countries - Birhan Ewunu Semagn; Abdulai Abubakari; Shimels Derso Kebede (BMC, 2023)
Abstract Background The consumption of Sugar-Sweetened Beverages (SSBs) has been linked to the global epidemic of obesity and chronic disease. Following the economic growth, urbanization, and attractive market for beverage companies, the consumption of SSBs is a rising public health challenge in low and middle-income countries. Hence, this study aimed to assess the magnitude of SSBs consumption and associated factors among women of reproductive age group in two SSA countries. Methods This cross-sectional study used data from Integrated Public Use Micro Data Series-Performance Monitoring for Action (IPUMS-PMA) with a total sample of 3759 women aged 15-49 years old in Burkina Faso and Kenya. The data was collected on June - August 2018 in Burkina Faso, and May -August 2018 in Kenya. SSBs consumption was measured by asking a woman if she drank SSBs yesterday during the day or night, whether at home or anywhere else. A mixed-effect logistic regression model was employed to identify associated factors. Result Half (50.38%) [95%CI; 46.04, 54.71] of women consumed SSBs. Sociodemographic characteristics like primary education (AOR = 1.35; 95%CI: 1.05-1.74), secondary education (AOR = 1.46; 95%CI: 1.13-1.90), being employed (AOR = 1.28; 95%CI: 1.05-1.56),and dietary characteristics like consumption of savory and fried snack (AOR = 1.61; 95%CI = 1.24-2.09), achieved minimum dietary diversity (AOR = 1.67; 95%CI: 1.38-2.01), moderate household food insecurity (AOR = 0.74, 95% CI: 0.58, 0.95), and sever household food insecurity (AOR = 0.71, 95% CI: 0.56, 0.89) had significant statistical association with SSBs consumption. Conclusion Consumption of SSBs among women in two Sub-Saharan African countries (Burkina Faso and Kenya) is high. Having higher educational status, being employed, achieved minimum dietary diversity, and having low/no household food in-security were found to be significantly associated with SSBs compared with their counterparts. We recommend for further study in other African countries using objective measurements of SSBs consumption.